1992
DOI: 10.1007/bf01960809
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four methods for rapid detection of adenovirus

Abstract: Four methods for rapid detection of adenovirus were evaluated by testing retrospectively 28 frozen clinical specimens from which an adenovirus strain had been isolated. After thawing all specimens were retested for the presence of adenovirus by conventional culture on KB cells and found to be positive. The four tests used for rapid detection of adenovirus were a 48-hour culture technique, and an immunoassay, a latex agglutination test and an immunofluorescence assay for direct detection of viral antigen using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…This antibody recognizes an epitope in the Nterminal of capsid protein VP1 that is conserved in the enterovirus genus. Its specificity and sensitivity for the detection of enteroviruses in epithelial cell culture and tissue samples have been the subject of prior reports [27,28]. In our study, positive staining with the anti-VP1 antibody was observed in 11 out of 12 pSS samples, 1 out of 8 sSS samples, and 0 out of 16 controls.…”
Section: Detection Of Single-stranded Rna Viruses In Psssupporting
confidence: 52%
“…This antibody recognizes an epitope in the Nterminal of capsid protein VP1 that is conserved in the enterovirus genus. Its specificity and sensitivity for the detection of enteroviruses in epithelial cell culture and tissue samples have been the subject of prior reports [27,28]. In our study, positive staining with the anti-VP1 antibody was observed in 11 out of 12 pSS samples, 1 out of 8 sSS samples, and 0 out of 16 controls.…”
Section: Detection Of Single-stranded Rna Viruses In Psssupporting
confidence: 52%
“…Techniques using spin amplification and identification by a specific monoclonal antibody have been shown to shorten significantly the detection time of many viruses in cell culture, including cytomegalovirus [Agha et al, 1988;Alpert et al, 1985;Gleaves et al, 1984;Pozzetto et al, 1990], adenovirus [August and Warford, 1987;Trabelsi et al, 1992] sensitivity and specificity. In this study, the combined effect of sample centrifugation and immunological staining is probably responsible for the dramatic increase in sensitivity of RCA compared to CCA in the first three days of virus replication, as exemplified by the data in Table IV.…”
Section: Discussionmentioning
confidence: 99%
“…This disadvantage could be avoided by the combination of two RCA on the same samples using enterovirus and adenovirus group-specific monoclonal antibodies; in fact, we have already shown that a similar technique can be applied to adenoviruses [Trabelsi et al, 1992]. Further such studies are under development in our laboratory.…”
mentioning
confidence: 87%
“…The rapid 48-h culture technique was performed by using 96-well plate centrifugation and immunoperoxydase staining with adenovirus monoclonal antibody (H-60 clone, Argene, France) as previously reported [3]. Conventional cell culture plates were observed periodically for cytopathic effects.…”
Section: Methodsmentioning
confidence: 99%